Liquid Religiosity in the Digital Space: A Critical Discourse Analysis of Instagram Content by Akal Indonesia - Al Hakim, Zaidan Ahmad Dzulfikar; Rahayu, Mustaghfiroh (LP2M IAIN kUDUS, 2026)
This study analyzes how digital discourse practices in the Instagram content of Akal Indonesia (@akal.indo) recontextualize religious messages, thereby constructing liquid religiosity in contemporary digital society. The research employs a qualitative approach using Norman Fairclough’s three-dimensional Critical Discourse Analysis, while Zygmunt Bauman’s Liquid Modernity serves as the interpretative framework at the level of social practice. The data consist of seven purposively selected Instagram carousel posts. The findings reveal that religious recontextualization operates through four discourse patterns: religion in everyday life, the integration of religious language with popular psychology, religion as a space for self-reflection and self-management, and the negotiation of religious authority. This study proposes a mechanism of religious recontextualization in digital spaces as a conceptual framework for understanding the transformation of religiosity in modern digital society.